PKM PEMBERDAYAAN KELOMPOK PETANI MELALUI PENERAPAN PEMANGKASAN YANG BENAR PADA KELOMPOK TANI SOLOK BIO-BIO DI NAGARI SOLOK BIO-BIO KECAMATAN HARAU KABUPATEN LIMA PULUH KOTA - Yuli, Yuliatri (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
This community service activity aimed to enhance farmers’ capacity in cocoa crop maintenance through training on cultural techniques of pruning. The activity was conducted on October 3, 2025, in Nagari Solok Bio-Bio, Harau District, Lima Puluh Kota Regency, involving 20 members of the Solok Bio-Bio Farmers Group. The methods used included counseling, group discussions, field demonstrations, and hands-on pruning practices on cocoa plants. The results showed that the training effectively improved farmers’ knowledge and skills in identifying branches that need to be pruned, applying proper pruning techniques, and maintaining sanitation of tools and plantations. Participants demonstrated high enthusiasm and active participation throughout the activity. The training not only improved technical competence but also fostered teamwork, collaboration, and commitment among farmers to apply appropriate pruning techniques sustainably in their own plantations. Overall, this program had a positive impact on increasing the capacity of cocoa farmers in Nagari Solok Bio-Bio. The adoption of proper pruning practices is expected to enhance cocoa productivity, plant health, and bean quality at the farmer level.